2021
DOI: 10.3389/fpsyg.2021.592925
|View full text |Cite
|
Sign up to set email alerts
|

Exploration of Social Benefits for Tourism Performing Arts Industrialization in Culture–Tourism Integration Based on Deep Learning and Artificial Intelligence Technology

Abstract: As a product of the tourism performing arts industry in culture–tourism integration development, to develop a featured culture–tourism town is a new trend for tourism development in the new era. To analyze the social benefit of the culture–tourism industry, in this study, an artificial intelligence model for social benefit evaluation is constructed based on backpropagation (BP) neural network and fuzzy comprehensive analysis, with Yiyang Town taken as an example. The criterion layer in the model includes three… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…On the other hand, a larger group of six articles addresses adaptability (Binson et al, 2024;Liu, 2023;Muhamad & Destianto, 2022;Parani et al, 2024;Shahnaz & Muhamad, 2022;Zhang, 2021), underscoring the importance of cultural tourism sectors ability to respond to changing environmental, social, and technological contexts. This adaptability is crucial for destinations to maintain relevance and competitiveness in the global tourism market, ensuring they can quickly adjust to both global trends and local needs.…”
Section: Adaptabilitymentioning
confidence: 99%
“…On the other hand, a larger group of six articles addresses adaptability (Binson et al, 2024;Liu, 2023;Muhamad & Destianto, 2022;Parani et al, 2024;Shahnaz & Muhamad, 2022;Zhang, 2021), underscoring the importance of cultural tourism sectors ability to respond to changing environmental, social, and technological contexts. This adaptability is crucial for destinations to maintain relevance and competitiveness in the global tourism market, ensuring they can quickly adjust to both global trends and local needs.…”
Section: Adaptabilitymentioning
confidence: 99%
“…Sustainable regional development will increase competitiveness. The new infrastructure for tourism has a positive impact (R. Zhang, 2021). With the same vision between government and community policies, the tourism potential in rural areas can be increased again (Nelson et al, 2021).…”
Section: Socialmentioning
confidence: 99%
“…The result also showed that tourism will increase the country's foreign trade turnover. More advanced methods were explored in tourism domain in China [29] with social evaluation index as the attributes and hybrid methods of back propagation and fuzzy as the model.…”
Section: B Prediction In Tourist Domainmentioning
confidence: 99%